The Freedom of Expression of Judges’ Communication - Carlos Manuel Rosales (Fakultas Hukum, Universitas Internasional Batam, 2022)
It is essential that the judicial function be public, discreet and professional. Its legitimacy as a public authority is obtained through the recognition of judgments, in which there is an identification between decisions and society. But what type of communication must be made by the judiciary, and especially by judges to provide information about their activities, and that their interaction strengthens the republic, generating proximity between the sovereign and the public power. Freedom of expression is a human right held by all people, but it is not absolute. In the case of judges, they do not enjoy this prerogative in the same way as citizens, since their commission subjects them to a special order (right of association, assembly, expression, privacy, among others). His investiture and decisions should leave no bias that he is not independent or impartial, that legality is his ruling principle, and that his personal affairs should not transcend his private sphere. Their prudence and wisdom should not only be part of their resolutions, but also part of their public acts. This research is not an attempt to curb the freedom of expression of the judges or to impose a gag or restrict the right of the parties and society to information.